2016
DOI: 10.1002/ajoc.201600109
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Double Decarboxylative Coupling Reactions of Alkynyl Carboxylic Acid and Glyoxylic Acid: Synthesis of Propargyl Amines and Imidazopyridines

Abstract: The reactiono fa lkynyl carboxylic acids, glyoxylic acid derivatives, and amines in the presence of ac opper catalyst afforded the corresponding propargyl amines in good yields. The alkynyl carboxylic acid of this coupling reaction shows similarr eactivity to that of at erminal alkyne, and the reactivityo ft he glyoxylic acid is almost identicalt ot hat of an aldehyde. When 2-aminopyridine was employed as the amine source, imidazopyridine derivatives weref ormedi n good yields.Scheme1.Different approaches to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…We have reported both metal‐free and copper‐catalyzed decarboxylative coupling reactions between alkynoic acids, amines, and aldehydes (Scheme 1c) [24] . Furthermore, we have reported that the doubly decarboxylative coupling reaction of phenylglyoxylic acids, alkynoic acids, and amines affords the corresponding propargylamines in the presence of a copper catalyst (Scheme 1c) [25] …”
Section: Methodsmentioning
confidence: 99%
“…We have reported both metal‐free and copper‐catalyzed decarboxylative coupling reactions between alkynoic acids, amines, and aldehydes (Scheme 1c) [24] . Furthermore, we have reported that the doubly decarboxylative coupling reaction of phenylglyoxylic acids, alkynoic acids, and amines affords the corresponding propargylamines in the presence of a copper catalyst (Scheme 1c) [25] …”
Section: Methodsmentioning
confidence: 99%
“…Our group also observed that aldehydes can be replaced by glyoxylic acids to synthesize propargylamines by using A 3 coupling reactions (Scheme 39). 46 The reaction was conducted in toluene at 110 °C and provided good product yields. Further, imidazopyridines were produced in good yields when 2-aminopyridines were employed as the amine source.…”
Section: Scheme 36 Synthesis Of Propargylamines Under Metal-free Condmentioning
confidence: 99%
“…In 2016, an extension to glyoxylic acid derivatives as substrates instead of aldehydes was reported by Lee and co‐workers also relying on the use of CuI catalyst. [ 23 ] Upon treatment with 10 mol% of CuI in toluene, various alkynyl carboxylic acids 20 , secondary aliphatic amines 21 , and oxophenylacetic acid 22 underwent coupling to give the corresponding propargylamines 23 in moderate to almost quantitative yields (Scheme 9). The protocol also allowed the synthesis of imidazopyridine derivatives employing 2‐aminopyridine as the amine source.…”
Section: Metal‐catalyzed Reactionsmentioning
confidence: 99%